2002
DOI: 10.1106/073168402025787
|View full text |Cite
|
Sign up to set email alerts
|

Delaminated Woven Fabric Composite Plates under Transverse Quasi-Static Loading: Experimental Studies

Abstract: Laminated composite plates are very sensitive to transverse loading because of weak interfaces between layers. During transverse loading, delamination can initiate and propagate at the interfaces. Also, in-plane failure of layers can initiate and grow further because of the in-plane stresses. Such damages can cause severe structural disintegration leading to a reduction in stiffness and strength. The delamination may be caused by manufacturing defects also. Such delamination can grow during service condition. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…As shown in Figure 14(b), there is barely indentation damage of fiber bundles and resin matrix for Specimen F-10. As the indentation load increases up to 20 kN, fiber bundle damage, fiber debonding and fiber breakage can be observed 35 as in Figure 14(c) and (d). From Figure 14(e), it is revealed that the serious internal damage leads to the collapse of composite specimen.…”
Section: Micro-ct and Sem Characterization Of Damaged Specimensmentioning
confidence: 89%
“…As shown in Figure 14(b), there is barely indentation damage of fiber bundles and resin matrix for Specimen F-10. As the indentation load increases up to 20 kN, fiber bundle damage, fiber debonding and fiber breakage can be observed 35 as in Figure 14(c) and (d). From Figure 14(e), it is revealed that the serious internal damage leads to the collapse of composite specimen.…”
Section: Micro-ct and Sem Characterization Of Damaged Specimensmentioning
confidence: 89%
“…The experimental results for specimen SP2 are presented in Figure 3 and Table 11 (Naik and Reddy, 2002). Damage dimensions under transverse central quasi-static patch loading are presented in Table 11.…”
Section: In-plane Damage Evolutionmentioning
confidence: 99%
“…Composite plates of dimensions 150 Â 150 Â 5 mm 3 made of a typical plain weave E-glass/epoxy laminate GLE-12 were used for the experimental studies under transverse central quasi-static patch loading (Naik and Reddy, 2002). Central artificial delamination of 5 mm diameter at a distance of 1 mm from the top surface was introduced.…”
Section: Appendixmentioning
confidence: 99%
See 2 more Smart Citations